River Basin Management - Bucur, Daniel (IntechOpen, 2016)
Many of the challenges facing farmers and human communities from hydrographical basins are not new. But, due to the fact that the nature and extents of the problems vary from one region to another and from one basin to another, the responses are highly diversified. There is no generally valid solution for all the problems. However, in addressing issues on ensuring the prevention or mitigation of the destructive consequences of flood damage or prolonged drought as for the optimal use of water by consumers, sustainable basin land use, biodiversity conservation, and environment protection as well, fourteen specialists and their colleagues present the state of the art in these important matters and new possible solutions to solve, identified from the scientific investigations undertaken.